Komunikasi Antar Pribadi Antara Orang Tua dan Anak dalam Masa Pandemi Covid-19 - Julius Bintang Saputra; Satya Candrasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Communication in the family is something that can affect the behavior of children in society. Communication that occurs in the family changes greatly influenced by several factors, including the length of time to meet and also how to communicate. Interpersonal communication within the family has changed during the COVID-19 pandemic. Communication changes as the time or intensity of meeting increases. This study aims to find out how communication occurs during the covid 19 pandemic and also the obstacles that occur when communicating during the covid 19 pandemic, and also to see the violence that occurs in children both verbally and physically. In this study, researchers used the theory of symbolic interactionism. This research uses constructivism paradigm as well as qualitative approach, and interview method. Data were obtained using observation and interview techniques. The result of this study is that communication within the family does not change, only the time of meeting changes. The obstacle faced during communication within the family during a pandemic is saturation, where they meet for 24 hours every day, besides that, there are also obstacles faced by gadgets.